Smart Farming System Design Based on Long Range and Internet of Things - Rifki Fauzan Anshori; Muhammad Saleh; Abqori Aula (Journal of Computer Science and Informatics Engineering, 2025)
Mustard greens require an efficient irrigation system to support optimal growth and increase productivity. One irrigation system that can be used is a drip irrigation system. This study designs a smart farming system based on the Internet of Things (IoT) and Long Range (LoRa) technology to automatically manage drip irrigation in mustard greens. This smart farming system uses a capacitive soil moisture sensor to monitor soil moisture, a soil pH sensor to monitor soil pH, and an HC-SR04 ultrasonic sensor to monitor the water level in the water tank. The microcontroller used in this smart farming system is ESP32 and the communication module used is LoRa SX1278. This smart farming system uses a drip irrigation system that will be displayed on the Blynk application. This system allows remote monitoring of plant conditions and automatic drip irrigation based on soil moisture levels. The results of testing the smart farming system using a drip irrigation system showed the accuracy of the ultrasonic sensor to measure water levels of 96.71%, the soil moisture sensor to measure soil moisture levels of 95.65%, and the soil pH sensor to measure soil pH of 97.46%. Communication using LoRa in areas with minimal interference can reach a distance of up to 321.66 meters. While in areas with a lot of interference it can reach a distance of up to 100 meters. The average LoRa data transmission time is 3.185 seconds